Integrating Modified English Songs to Improve Vocabulary Retention: A Pre-experimental Study with Grade-7 EFL Learners in Indonesia - Melinda; Sunra, La; Farahdiba, Syarifah (Celebes Journal of Language Studies, 2025)
This pre-experimental study explores the effectiveness of integrating modified English songs in enhancing vocabulary retention among seventh-grade EFL learners in Indonesia. The research was conducted with 25 students at SMPN 3 Minasatene using a one-group pre-test–post-test design. The intervention consisted of five instructional sessions incorporating songs whose lyrics were deliberately adapted to match thematic vocabulary categories (objects, body parts, shapes, and vegetables). Each session combined listening, singing, contextual vocabulary practice, and short individual performances to reinforce lexical recall. Quantitative results revealed a significant improvement in learners’ vocabulary mastery, with the mean pre-test score (M = 69.64, SD = 5.95) increasing to the post-test mean (M = 89.12, SD = 6.31). The normalized gain (<g> = 0.64) indicates a high level of effectiveness based on Hake’s criteria. Qualitative observations further suggest that using modified songs enhanced learner motivation, enjoyment, and confidence in using English vocabulary. The findings demonstrate that purposeful integration of contextualized and culturally relevant songs can serve as an engaging medium for vocabulary development in early secondary EFL contexts. Pedagogical implications and recommendations for future experimental research designs are also discussed.